2021
DOI: 10.31590/ejosat.977591
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Fe/SBA-15 Heterogeneous Catalysts for Methyl Acetate Production

Abstract: In the present study, the synthesis of SBA-15 (Santa Barbara Amorphous) support material(SPm) was initially carried out with the method determined according to the literature research. The catalytic property of SBA-15 was imparted by the hydrothermal method (HtM), different from the traditionally applied impregnation method. In this method, the active substance (iron III oxide; Fe2O3) was added to the solution during the synthesis of the SPm. The amount of active substance in the synthesized catalysts was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Figure 2 shows the results of the low and high-angle XRD analysis of the SBA-15 and the hybrid samples consisting of different loadings of TiO 2 , Fe, and Cd on SBA-15. Similar results are shown in our previous work dealing with the activities of Cd/SBA-15 for the esterification of acetic acid with methanol [27,28]. According to the results of the XRD analysis of the SBA-15, four main Bragg peaks were obtained (Figure 2a), corresponding to the d(100), d(110), d(200) [29,30], d(210) [31], and d(300) [32] characteristic peaks.…”
Section: Xrd Analysissupporting
confidence: 88%
See 3 more Smart Citations
“…Figure 2 shows the results of the low and high-angle XRD analysis of the SBA-15 and the hybrid samples consisting of different loadings of TiO 2 , Fe, and Cd on SBA-15. Similar results are shown in our previous work dealing with the activities of Cd/SBA-15 for the esterification of acetic acid with methanol [27,28]. According to the results of the XRD analysis of the SBA-15, four main Bragg peaks were obtained (Figure 2a), corresponding to the d(100), d(110), d(200) [29,30], d(210) [31], and d(300) [32] characteristic peaks.…”
Section: Xrd Analysissupporting
confidence: 88%
“…The FT-IR analysis of SBA-15 showed that the peaks between wavelengths of 445 cm −1 and 1046 cm −1 belonged to the characteristic structure of SBA-15 (Figure 3) [27,28]. Symmetrical and asymmetrical structures of tensile and flexible vibrations of Si-O and SiO 2 were observed at 938, 789, and 1044 cm −1 [37,38].…”
Section: Ft-ir Analysismentioning
confidence: 96%
See 2 more Smart Citations